2017
DOI: 10.1080/10837450.2017.1329835
|View full text |Cite
|
Sign up to set email alerts
|

Design and in vitro evaluation of tenofovir-loaded vaginal gels for the prevention of HIV infections

Abstract: Infection with the human immunodeficiency virus (HIV) is affecting women disproportionally with increasing incidence rates over the last decades. Tenofovir is one of the most commonly used antiretroviral agents, which belongs to the nucleoside/nucleotide reverse transcriptase inhibitor family, for the prevention of HIV acquisition. In scope of this study, a thermogelling system containing tenofovir-loaded chitosan nanoparticles for the controlled release of tenofovir was developed and characterized. The in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Timur et al combined the mucoadhesive properties of chitosan and the thermo-sensitive characteristics of poloxamer 407, in order to develop a thermo-gelling system containing chitosan nanoparticles for the vaginal delivery of tenofovir (TFV), an antiviral agent that is used in the treatment of the human immunodeficiency virus (HIV) [ 130 ]. An amount of TFV was entrapped in the gel, with the aim of controlling the leakage of drugs from the nanoparticles.…”
Section: Poloxamer 407-based Mucoadhesive Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Timur et al combined the mucoadhesive properties of chitosan and the thermo-sensitive characteristics of poloxamer 407, in order to develop a thermo-gelling system containing chitosan nanoparticles for the vaginal delivery of tenofovir (TFV), an antiviral agent that is used in the treatment of the human immunodeficiency virus (HIV) [ 130 ]. An amount of TFV was entrapped in the gel, with the aim of controlling the leakage of drugs from the nanoparticles.…”
Section: Poloxamer 407-based Mucoadhesive Formulationsmentioning
confidence: 99%
“…Both of these values were dramatically better than that obtained by the drug solution, which evidenced full leakage of the active compound over a 3 h period. The entrapment of TFV within the nanoparticles retained by the poloxamer-gel had two peculiar features: (1) the burst-release effect, induced by the presence of the free drug within the gel network, and (2) sustained drug leakage for up to 24 h due to the presence of the colloidal systems in the polymeric matrix [ 130 ].…”
Section: Poloxamer 407-based Mucoadhesive Formulationsmentioning
confidence: 99%
“…Thermogelling solutions containing tenofovir (TFV), an antiretroviral agent for the prevention of HIV acquisition, loaded into chitosan nanoparticles was prepared by Timur et al The P407 formulation containing chitosan nanoparticles had a Tgel of 26.6 °C which is slightly lower than the P407 20% w/v formulation with TFV only which was 28.2 °C . At 35 °C, the formulation containing nanoparticles had higher viscosity than the gel with the TFV only (100.24 Pa s and 87.8 Pa s, respectively) …”
Section: Poloxamer 407 Modification By the Use Of Polymer Additivesmentioning
confidence: 99%
“…Out of necessity, the findings have been simplified and the original articles should be consulted to fully understand the findings. Most studies report a decrease in Tgel when polymer or nanoparticle additives are incorporated into P407 solutions, which may be a result of the increased overall solute content. Whilst some studies report an increase in Tgel, this occurs only at lower (≈15% w/v) P407 concentration and low (≈<0.1% w/v) additive concentration.…”
Section: Poloxamer 407 Modification By the Use Of Polymer Additivesmentioning
confidence: 99%
“…It is reported that prolonged carrier retention and extended drug release could be achieved by gel because of its better mucosal adhesion and superior gel strength (Mei et al, 2017;Timur et al, 2017;Tugcu-Demiroz, 2017). However, the application of gel in vaginal drug delivery is limited by its low penetration efficiency to the deep vaginal rugae because of its high viscoelasticity (Caramella et al, 2015;Johal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%